2012
DOI: 10.1128/jb.00099-12
|View full text |Cite
|
Sign up to set email alerts
|

RNase III Controls the Degradation ofcorAmRNA in Escherichia coli

Abstract: cIn Escherichia coli, the corA gene encodes a transporter that mediates the influx of Co 2؉ , Mg 2؉, and Ni 2؉ into the cell. During the course of experiments aimed at identifying RNase III-dependent genes in E. coli, we observed that steady-state levels of corA mRNA as well as the degree of cobalt influx into the cell were dependent on cellular concentrations of RNase III. In addition, changes in corA expression levels by different cellular concentrations of RNase III were closely correlated with degrees of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The predicted secondary structure of the hairpin was confirmed by analyzing the cleavage patterns of the model hairpin RNA after RNase T1 digestion. The other minor cleavage products observed might have resulted from the intrinsic ability of RNase III to randomly cleave RNA transcripts at high RNase III concentrations (8)(9)(10). We also synthesized a 3=-end 32 P-labeled model hairpin and performed an in vitro cleavage assay.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The predicted secondary structure of the hairpin was confirmed by analyzing the cleavage patterns of the model hairpin RNA after RNase T1 digestion. The other minor cleavage products observed might have resulted from the intrinsic ability of RNase III to randomly cleave RNA transcripts at high RNase III concentrations (8)(9)(10). We also synthesized a 3=-end 32 P-labeled model hairpin and performed an in vitro cleavage assay.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide analyses of Escherichia coli transcripts indicated that the abundance of a large number of mRNA species is regulated by RNase III (4,5). The abundance of several E. coli mRNA transcripts is dependent on the endoribonucleolytic activity of RNase III, including rnc (6), pnp (7), bdm (8), betT (9), corA (10), proU (11), mltD (12), and rng (4). Studies indicate that a subgroup of mRNA transcripts encoding factors associated with the cellular response of E. coli to osmotic stress is regulated by RNase III (8,9,11).…”
mentioning
confidence: 99%
See 3 more Smart Citations